TOLERANCE LIMITATION IN FACING RELIGIOUS DIVERSITY BASED ON THE TEACHING OF ISLAM - Muhammad Hifdil Islam (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Diversity becomes a necessity in the continuity of human life both from a group to a nation. However, lack of understanding among difference people can be an obstacle that will lead to conflict in public life. In contrast, diversity can become benefits factor in the life of society. And Religion is part of diversity that can become source of conflict between people. Islam as the religion of rahmatan lil'alamin (blessing for the whole universe), from the beginning despite having affirmed that the true religion is Islam, but in principle and social life, Islam recognizes religious entities, other religions and allow their followers to perform and practice their own worship. This paper explains how Islam gives a great respect for religious diversity and teaches the follower to be tolerant to other religion. In this paper, also explained how Al-Qur’an as main source of teaching in Islam gives the description of tolerance in religious diversity and it is supported by the argument of some of scholar of Islam. This paper reminds us that religious appreciation and practice does not stop at the stage of “I” exclusiveness claims that lead to a personal relationship with God, nor at “YOU” inclusiveness stage that mix the teaching all of religion but at the openness of “WE”, where religious appreciation of human values is emphasized (humanist and tolerance) without mix the religious sacredness .